FERTILITY DIFFERENTIALS AMONG ETHNIC GROUPS IN KOGI STATE, NIGERIA (2021)
Fertility differentials, which are variations in birth rates among population sub-groups, have largely accounted for the difficulty in formulating a workable population policy in Nigeria. Previous studies on fertility differentials in Nigeria focused mainly on three major ethnic groups – Hausa, Igbo and Yoruba. However, little attention has been given to minority ethnic groups, especially in Kogi State which has more than eight ethnic groups. This study was, therefore, designed to examine fertility levels, contraceptive knowledge and use, and male roles in fertility (contraceptive, sex preference, and family size decisions) among ethnic groups in Kogi State.